Kaposiform lymphangiomatosis effectively treated with MEK inhibition. Issue 10 (7th September 2020) - Foster, Jessica B; Li, Dong; March, Michael E; Sheppard, Sarah E; Adams, Denise M; Hakonarson, Hakon; Dori, Yoav
Abstract: Kaposiform lymphangiomatosis (KLA) is a rare lymphatic anomaly primarily affecting the mediastinum with high mortality rate. We present a patient with KLA and significant disease burden harboring a somatic point mutation in the Casitas B lineage lymphoma ( CBL ) gene. She was treated with MEK inhibition with complete resolution of symptoms, near‐complete resolution of lymphatic fluid burden, and remodeling of her lymphatic system. While patients with KLA have been reported to harbor mutations in NRAS, here we report for the first time a causative mutation in the CBL gene in a patient with KLA, successfully treated with Ras pathway inhibition. Synopsis: Report of a patient with the rare lymphatic anomaly, Kaposiform lymphangiomatosis (KLA). CBL proto‐oncogene mutation was identified and she was successfully treated by targeting the MAP kinase pathway. Identification of CBL mutation driving KLA. Patient successfully treated with MEK inhibition. Abstract : Report of a patient with the rare lymphatic anomaly, Kaposiform lymphangiomatosis (KLA). CBL proto‐oncogene mutation was identified and she was successfully treated by targeting the MAP kinase pathway.